ArticleFTIR Determination of MiconazoleEffects on Mice Fetus Brain Tissue: FTIR determination of Miconazole effects on Mice fetus brain tissue - Azadeh Ashtarinezhad; Ataollah Panahyab; Baharak Mohamadzadehasl; Hossein Vatanpour; Farshad H. Shirazi (Iranian Journal of Pharmaceutical Sciences, 2014)
Miconazole is an imidazole antifungal agent, commonly applied topically to the skin or mucous membranes. The aim of this study was to examine the alternative method for gaining mechanism or the bimolecular changes caused by the possible teratogenic effects of Miconazole on mice fetus brain tissueusing FTIR-Microspectroscopy.The mice were injected with Miconazole(60 mg/Kg) on gestation day 9. Fetuses were dissected on day 15 of gestation and morphological and histological studies on thefetus were carried out. Sections (10 μm) of controland Miconazoletreated fetus brain tissue were used for FTIR measurement in the mid-infraredregion. The results were shown by spectra2ndderivativeand also subtracting from control spectra.A lower intensity in the lipid (2800–3000 cm-1) and amid I (1600–1800 cm-1) regions of Miconazole treated mice fetus brain tissue was observed compared to the control mice fetus brain tissue. No major spectral shifting was observed at amide I band, amide II band and nucleic acid regions.As a conclusion, FTIR-Microspectroscopycan be a useful tool forteratogenic measurement with a unique ability to identify the modified bimolecular structuresin mice fetus tissues.